Prospects for the Development of Bond Circulation in the Capital Market - Sobirov, Jurabek (GREEN ECONOMY AND DEVELOPMENT, 2024)
This article explores the prospects for enhancing bond market development in developing economies. It delves into the significance of bond markets, examines global experiences, and provides tailored recommendations to address challenges and leverage opportunities. By focusing on regulatory frameworks, market infrastructure, investor education, and government leadership, this article aims to guide developing countries in nurturing vibrant bond markets. These markets hold the potential to mobilize capital, promote economic diversification, ensure financial stability, and facilitate critical infrastructure financing.